Dampak Metode Pembelajaran Pada Siswa Kelas III Sdn 1 Ketitang: Minat Baca - Vindi Septianingrum (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This This research aims to describe the impact of mindmapping learning methods onstudents of grade III SDN 1 Ketitang, especially on reading interests. The study took placeusing descriptive qualitative research and using methods of measuring interview andobservation data. The main subject of this study was the students of class III SDN 1Ketitang consisting of 15 students and 1 teacher. To test the validity of the data in thisstudy used a credibility test of triangulation techniques and triangulation of sources. Theresults showed that there were differences in the results of students' reading interest inlearning after the application of the mindmapping method. This is evident from theactiveness and participation of students in participating in learning activities using themindmapping method, which is when teachers allow students to explore and find out forthemselves the student's interest in which reading they like.